1999
DOI: 10.1073/pnas.96.13.7226
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the yeast U4/U6⋅U5 small nuclear ribonucleoprotein particle and identification of its proteins

Abstract: The yeast U4͞U6⅐U5 pre-mRNA splicing small nuclear ribonucleoprotein (snRNP) is a 25S small nuclear ribonucleoprotein particle similar in size, composition, and morphology to its counterpart in human cells. The yeast U4͞ U6⅐U5 snRNP complex has been purified to near homogeneity by affinity chromatography and preparative glycerol gradient sedimentation. We show that there are at least 24 proteins stably associated with this particle and performed mass spectrometry microsequencing to determine their identities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
147
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(157 citation statements)
references
References 57 publications
10
147
0
1
Order By: Relevance
“…Neither protein was reported in the U4/ U6.U5 tri-snRNP particle with Prp38p (Stevens and Abelson 1999;Stevens et al 2001) and we find that fulllength constructs of Cwc23p and Sqs1p fail to interact with Prp38p by the two-hybrid method (data not shown). In addition, when selected under conditions that release Prp38p from the tri-snRNP particle (Xie et al 1998), Prp38p copurifies as a three-component complex with the Spp381p and Snu23p splicing factors without Cwc23p or Sqs1p ( Figure S4).…”
Section: Resultssupporting
confidence: 45%
“…Neither protein was reported in the U4/ U6.U5 tri-snRNP particle with Prp38p (Stevens and Abelson 1999;Stevens et al 2001) and we find that fulllength constructs of Cwc23p and Sqs1p fail to interact with Prp38p by the two-hybrid method (data not shown). In addition, when selected under conditions that release Prp38p from the tri-snRNP particle (Xie et al 1998), Prp38p copurifies as a three-component complex with the Spp381p and Snu23p splicing factors without Cwc23p or Sqs1p ( Figure S4).…”
Section: Resultssupporting
confidence: 45%
“…1+ H-complex (this study)+ 2+ A/B-complex (Bennett et al+, 1992a)+ 3+ A/B-complex (Neubauer et al+, 1998)+ 4+ S. cerevisiae tri-snRNP (Gottschalk et al+, 1999)+ 5+ S. cerevisiae tri-snRNP (Stevens & Abelson, 1999)+ 6+ Human CDC5 complex (Ajuh et al+, 2000)+ 7+ C-complex (this study)+ ⅙ : proteins identified in this study by a single unique peptide only+…”
Section: Ms Jurica Et Almentioning
confidence: 80%
“…The complexes characterized by Bennett et al+ and Neubauer et al+ both contained a number of proteins involved in early spliceosome assembly, but not found in our C complex preparation+ These include some U1 snRNP proteins and first-step factors (see above)+ B and C complexes do share the core U2 and U5 snRNP proteins, as well as Prp19, SKIP, p68, CDC5, and PRL1+ However, a number of uncharacterized proteins found by Neubauer et al+ were not identified in C complex+ Several proteins shared between B and C complexes were also found associated with the tri-snRNP (U4/U6+U5) from Saccharomyces cerevisiae by mass spectrometry (Gottschalk et al+, 1999;Stevens & Abelson, 1999)+ These studies found the majority of Sm, LSM, and U5 snRNP proteins, as well as several new tri-snRNP proteins+ One of these, SART1, is present in C complex but was not identified in B complex+ The tri-snRNP associated proteins Prp3 and Prp4 are found in B complex, but Prp4 was identified by only a single peptide in C complex+ A U4/U6 associated protein, Prp4 has been shown to join the spliceosome as part of the tri-snRNP, but it appears to depart with U4 snRNA during the transition to C complex (Ayadi et al+, 1997)+ Also listed in Table 2 are proteins associated with the CDC5 protein, first identified as a novel spliceosome component in the mass spectrometry analysis of B complexes (Neubauer et al+, 1998)+ This protein has also been shown to associate with a 40S complex from Schizosaccharomyces pombe where it is essential for pre-mRNA splicing (Burns et al+, 1999;McDonald et al+, 1999)+ The 40S S. pombe complex also contains homologs to U5-220 (Prp8) and U5-116, as well as SmD2, Prp19, Prp5, Syf1, and Ecm2 (Slt11)+ Like C complex, the 40S S. pombe complex contains U2, U5, and U6 snRNAs, but no U1 or U4 (McDonald et al+, 1999)+ Mass spectrometry of immunopurified CDC5 complex from HeLa cells identified Sm proteins and U1 and U2 snRNP proteins, as well as a number of other splicingassociated proteins (Ajuh et al+, 2000)+ In the mammalian system, no U5 or tri-snRNP proteins were identified, although splicing intermediates were immunoprecipitated with CDC5+ Of the proteins associated with mammalian CDC5 that had not been previously linked to splicing, only one, HSP148, was also found in our C complex preparation+…”
Section: Purification Of Native C Complex Spliceosomesmentioning
confidence: 99%
“…To explore the interaction between the U6 telestem and Prp24 protein in yeast, we first investigated whether Prp24 protein is active and important for spliceosome assembly in yeast extracts+ During spliceosome assembly, naked yeast U6 snRNA is complexed by Lsm2-8 and Prp24 proteins to form free U6 snRNP (Stevens et al+, 2001)+ The Prp24 component of free U6 snRNP is thought to be important for promoting duplex forma-59 and 39 domains of yeast U6 snRNAtion between free U6 and free U4 snRNPs to produce U4-U6 di-snRNP and U4-U6•U5 tri-snRNP complexes, at least for Prp24 protein in free U6 snRNPs recycled after a round of splicing (Raghunathan & Guthrie, 1998a)+ During the assembly of U4-U6•U5 tri-snRNP, Prp24 is dissociated from U6 snRNP or is much less tightly associated with it (Shannon & Guthrie, 1991;Gottschalk et al+, 1999;Stevens & Abelson, 1999)+ Formation of U4-U6•U5 tri-snRNP was previously shown to be necessary for spliceosome assembly and splicing (Fetzer et al+, 1997), and tri-snRNP can bind premRNA to assemble spliceosomal complexes in the presence of ATP in vitro (Raghunathan & Guthrie, 1998a)+ However, it was not known whether Prp24 plays a role in the biogenesis of U6 snRNP and tri-snRNP, as studying this process was complicated by the predominance of fully formed and/or recycled U6-containing snRNPs in extract+ In the experiments reported here, endogenous epitope-tagged Prp24(HA) 3 protein in yeast extract was immunodepleted, and this depletion diminished the assembly of 32 P-labeled U6 RNA into de novo tri-snRNPs to 14-16% of mock-depletion levels+ Addition of recombinant Prp24 restored tri-snRNP assembly to 75-97% of mock-depletion levels in replicate assays (Fig+ 6A)+ Endogenous U6 snRNA in these samples was RNase H digested prior to immunodepletion or mock depletion of Prp24 protein, thus to avoid codepletion of U6 snRNP-associated proteins, including Lsm2-8 proteins+ Thus, we found that Prp24 is functional in catalyzing the assembly of naked U6 snRNA into U4-U6•U5 tri-snRNPs during snRNP biogenesis+ Furthermore, this function is important for tri-snRNP assembly in vitro+ Continuing our exploration of the relationship between the U6 telestem and Prp24 protein, we constructed mutant U6 RNAs with mutations that disrupt telestem base pairings+ We also constructed some with additional compensatory mutations that can restore base pairing+ Of those that potentially restore telestem base pairing, there were two types of mutational combinations: one type in which A-U base pairs of the telestem were inverted to U-A pairs, and another type in which A-U base pairs were transverted to G-C pairs that may hyperstabilize the telestem+ The base-pair restoring combinations did show a dramatic restoration of the binding interaction between mutant U6 RNA and Prp24(HA) 3 protein when the compensatory mutations were incorporated in the half of the telestem containing nt 36-39 and 92-95 (see Fig+ 1), that is, when the compensatory mutants U6+36-38polyA,93-95polyU and U6+36-38polyC,93-95polyG were individually assayed for coimmunoprecipitation with Prp24(HA) 3 (Table 4)+ The compensatory effect for these two U6 mutants was 50-fold and 25-fold, respectively+ Parallel controls corroborate that the compensatory effects were dependent on restoration of Watson-Crick base pairing rather than on various combinatio...…”
Section: Effects Of Truncating the 59 Or 39 Terminal Domain Of Yeast mentioning
confidence: 99%